Proteomic profiling of the endogenous peptides of MRSA and MSSA - Haixia Tu (PeerJ Inc., 2021)
Staphylococcus aureus is a Gram-positive bacterium that can cause diverse skin and soft tissue infections. Methicillin-resistant Staphylococcus aureus (MRSA) can cause more severe infections than methicillin-susceptible Staphylococcus aureus (MSSA). Nevertheless, the physiological and metabolic regulation of MSSA and MRSA has not been well studied. In light of the increased interest in endogenous peptides and recognition of the important roles that they play, we studied the endogenous peptidome of MSSA and MRSA. We identified 1,065 endogenous peptides, among which 435 were differentially expressed (DE), with 292 MSSA-abundant endogenous peptides and 35 MRSA-abundant endogenous peptides. MSSA-abundant endogenous peptides have significantly enriched “VXXXK” motif of at the C-terminus. MSSA-abundant endogenous peptides are involved in penicillin-binding and immune responses, whereas MRSA-abundant endogenous peptides are associated with antibiotic resistance and increased toxicity. Our characterization of the peptidome of MSSA and MRSA provides a rich resource for future studies to explore the functional regulation of drug resistance in S. aureus and may also help elucidate the mechanisms of its pathogenicity and the development of treatments.